Potencial hepatoprotetor e genoprotetor da própolis vermelha produzida por abelha (apis mellifera) no Rio Grande do Norte, Brasil - Silva, Jardel Bezerra da (2019)
At present, one of the health problems that is increasingly prominent worldwide is liver disease. This factor contributes to the pharmaceutical industry developing new hepatoprotective drugs and conducting research testing natural products that have potential hepatoprotective and that act to depress oxidative stress and stimulating protection against DNA damage. In Brazil, several studies on the hepatoprotective and genoproterobic activity of different propolis of Apis mellifera are carried out, however there are no studies with the red propolis produced in the semi-arid region of Rio Grande do Norte. Therefore, the present research had the objective of evaluating the hepatoprotective effect of the hydroethanolic extract of the red propolis produced by Apis mellifera bee, obtained from beekeepers in the semi - arid region of Rio Grande do Norte. The chemical composition and antioxidant activity of the bee propolis, the hepatoprotective potential, through the induction of experimental cirrhosis in rats were determined; in addition to the in vitro evaluation of the antineoplastic potential of propolis in human hepatic carcinoma cell line (HepG2), and also the potential genotype in normal cell line (L929), exposed to hydrogen peroxide (H2O2). The samples had total phenotype contents from 74.92 ± 0.51 to 141.07 ± 1.27 mg GAE / 100g, flavonoids from 2.42 ± 0.17 to 8.35 ± 0.28 mg QE / 100g and antioxidant activity IC50 of 129.10 ± 0.49 to 54.14 ± 1.50 μg / ml. The propolis extract did not present cytotoxicity in normal cells and presented antigenotoxic or genoprotective effect, with genotoxicity reduction percentages of 90.17% ± 3.01; 71.15% ± 2.64 and 43.07% ± 2.64, respectively, for the concentrations of 500, 250 and 100 μl / ml of the extract. The results of serum levels of alanine aminotransferase (ALT) and aspartate aminotransferase (AST) hepatic enzymes indicated that the hydroethanolic extract of propolis did not cause liver toxicity and exerted a hepatoprotective effect against hepatic damage induced by thioacetamide (TAA). Through the macroscopic and histological evaluation of livers, it was also possible to suggest that the extract of the propolis analyzed exerted a hepatoprotective effect on the severity of cirrhosis, since in the livers of the animals of the treated group it was possible to verify that the regenerative nodules characteristic of cirrhosis were smaller and more discrete, when compared to the animals in the cirrhotic group. Likewise, there was a significant reduction in the percentage of collagen in the treated group compared to the cirrhotic group, demonstrating the hepatoprotective effect of propolis, which was able to reduce damage to hepatocytes, although no statistical difference was observed in livers weight in the stereological analysis showed that there was a significant difference in the percentage of hepatocytes and collagens among these groups. Thus, it is concluded that the extract of red propolis presents a varied chemical composition and promising pharmacological activities, being outstanding the antioxidant, non-cytotoxic, genoprotective and hepatoprotective, since it exerted a hepatoprotective effect through the hepatic lesion induced by TAA